Evaluation framework for unified command plans : a documented briefing - Bracken, Paul J.; Winnefeld, James A., 1929-; Howe, Robert D. (Robert Dale), 1936-; Harrell, Margaret C.; Arroyo Center. Strategy and Doctrine Program; Rand Corporation; United States. Army. (Santa Monica, CA : RAND, 1993)
This report presents a formal process for evaluating Unified Command Plans (UCP) that assesses the likely performance of competing alternative UCPs in the near future by evaluating them against specific performance criteria. The performance criteria are effective use of military power, efficiency, responsiveness, crisis adaptability, simplicity, alliance responsibilities, regional expertise, and organizational interface. For demonstration purposes, the report presents four illustrative UCPs that bound the range of alternative approaches, along with three alternative world view/strategy pairs with which to compare the illustrative UCPs. The evaluation of the illustrative UCPs reveals that such an approach would be valuable in highlighting sources of disagreement as an aid to reaching conclusions about the alternatives. As an aid to discussing the adaptability of plans, the report presents alternative long-range futures in which the world is dramatically different from what is expected in the near future and in which the U.S. strategy might become more activist. Review of these alternatives indicates that any UCP should be designed with considerable emphasis on the ability to learn and adapt to changing conditions.
"Arroyo Center."
Includes bibliographical references (p. 93).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Unified operations (Military science) -- Evaluation; United States -- Armed Forces -- Organization